SAT0726-HPR Improvement of hand function, physical capacity and quality of life of systemic sclerosis patients after autologous hematopoietic stem cell transplantation. (12th June 2018) - Costa Pereira, K.R.; Elias, J.B.; Moraes, D.A.; Guimaraes, A.L.C.; Garcia, J.T.; Oliveira, M.C.; Leopoldo, V.; Zombrilli, A.F.; Costa, T.M.; Stracieri, A.B.P.; Simoes, B.P.; Oliveira, M.C.C.
Abstract : Background: Systemic sclerosis (SSc) is characterised by skin thickening and visceral involvement, leading to impairment of physical function, daily life activities and quality of life. Severe cases usually have poor prognosis, despite conventional immunosuppressive treatment. Autologous hematopoietic stem cell transplantation (AHSCT) has been investigated as treatment for patients with severe SSc and promotes reduction of skin thickening and at least stabilisation of visceral involvement. There are no reports in the literature addressing the influence of AHSCT on hand function and physical capacity of SSc patients. Objectives: To evaluate the impact of AHSCT on skin involvement, hand function, physical capacity and quality of life (QoL) of SSc patients. Methods: This is a prospective longitudinal study of a cohort of 27 SSc patients who underwent AHSCT at a University Hospital in the state of São Paulo, Brazil. Patients were evaluated before, and at 6, 12 and 24 months after transplant. The evaluations included modified Rodnan skin score (mRSS), hand function (hand-grip strength, finger-to-palm distance – FTP, range of motion measures, DASH and COCHIN questionnaires), mouth opening, six-minute walk test (6MWT) and quality of life questionnaire (SF-36). Results were subjected to statistical analyses and significance levels were established at p<0.05. Results: Twenty-seven patients were evaluated before and at 6 months after transplant, 22 of which were additionally evaluated at 12 months, and 13 patients at 24 months post-transplant. At 12 months after AHSCT, patients presented significant improvement of mRSS (p<0.01), hand grip strength (p<0.01), range of motion of hands (p<0.01, except for I metacarpophalangeal joints of both hands), FTP distance (p<0.01), DASH (p<0.01), COCHIN (p<0.01), mouth opening (p<0.01), 6MWT distance (p=0.01), and physical (p<0.01) and mental (p=0.02) components of the SF-36, when compared to pre-transplant evaluations. Significant correlations were observed between skin involvement and range of motion measures (dominant hand: R=−0.65, p<0.01; non-dominant hand: R=−0.59, p<0.01), and between the 6MWT distance and quality of life (R=0.62, p<0.01), and between DASH and quality of life (R=−0.48, p=0.03). Conclusions: AHSCT enhances the functional status of SSc patients, significantly improving skin involvement, hand function, physical capacity and quality of life. These results can be interpreted as positive outcomes of AHSCT for SSc. References: [1] van Laar, et al. JAMA2014;311(24):2490–8. [2] Del Papa, et al. Bone Marrow Transplantation2017;52:53–58. [3] Burt, et al. Lancet2013:381(9872):1116–24. [4] Sullivan, et al. N Engl J Med2018;378:35–47. Disclosure of Interest: None declared